Economic aspects of solution of the problem of noise in a working zone of the airport - Коновалова, Е. В. (Proceedings of National Aviation University (archive), 1999)
Considered are the main principles of economic estimation of the measures of reduction of aviation noise in the working zone of the airport, also the method of determining the costs of maintaining the production environment for noise condition and problem of estimation and assessment of costs necessary for efficient correction of acoustics in industrial zone